2002
DOI: 10.1055/s-2002-19330
|View full text |Cite
|
Sign up to set email alerts
|

Highly Brominated Norbornanes by Photobromination as Precursors for the Convenient Synthesis of 2,3,5,6-Tetrabromo- and 2,3,5,6-Tetramethoxy-substituted Norbornadienes

Abstract: H i g h l y b r o m i n a t e d N o r b o r n a n e s b y P h o t o b r o m i n a t i o nAbstract: An efficient synthesis is described for hexabromonorbornane by photobromination of norbornadiene. Double dehydrobromination of the hexabromide by t-BuOK affords in high yield 2,3,5,6-tetrabromonorbornadiene, its copper-assisted treatment with sodium methoxide leads to the 2,3,5,6-tetramethoxy derivative. The tetrabromide constitutes a valuable precursor for the preparation of functionalized tetrasubstituted norbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…). Cycloadditions to the double bond of the compounds such as norbornadiene derivatives were occurred form exo faces because of electron density . The electron density of isolated double bond belongs to benzonorbornadiene ( 4 ), and data (NMR and HRMS) of adducts 7a – d are consistent with the proposed structures.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…). Cycloadditions to the double bond of the compounds such as norbornadiene derivatives were occurred form exo faces because of electron density . The electron density of isolated double bond belongs to benzonorbornadiene ( 4 ), and data (NMR and HRMS) of adducts 7a – d are consistent with the proposed structures.…”
Section: Resultssupporting
confidence: 52%
“…Benzonorbornadiene ( 4 ) and homonorbornadiene ( 5 ) are norbornadiene derivatives and can be rearranged with reagents such as bromine because of their strained structure . Norbornadiene derivatives including nitrogen–oxygen atoms and their rearrangement products may be important.…”
Section: Introductionmentioning
confidence: 99%
“…Previous literature showed that a good number of methods are available for preparation of the p -peroxyquinols and that these methods included the use of oxygen and H 2 O 2 . However, despite their efficiency, these methods have not yet been applied extensively. Treatment of 3,4,5-trimethylphenol ( 120 ) with Oxone in a basic medium afforded p -peroxyquinol 131 in 93% yield (Scheme ).…”
Section: Miscellaneousmentioning
confidence: 99%
“…In their synthesis of macamides, Kelley and co-workers used this strategy to prepare diene 103 from (E/Z)-1,2-dibromoethene (8b) by reaction with organoaluminum reagent 102 (Scheme 29). 44 In this case, the remaining bromide was functionalized through lithiation, followed by nucleophilic attack on glutaric anhydride (104) to provide macamide precursor 105.…”
Section: Polyenesmentioning
confidence: 99%
“…Cakmak and co-workers obtained 2,3,5,6-tetramethoxynorbornadiene (207) as the sole product when they performed the Cu-assisted C-O bond formation between 2,3,5,6-tetrabromonorbornadiene (206) and sodium methoxide (Scheme 61). 104 Zhou and co-workers took advantage of microwave irradiation to perform a similar reaction and transform 2,3-di-halo-1,4-naphthoquinones (84) into 2,3-dihydroxy-1,4naphthoquinone (209), using aqueous potassium hydroxide as the nucleophile and with CuCl 2 /proline lithium salt (208) as the catalyst (Scheme 62). 105…”
Section: Enols and Enol Ethersmentioning
confidence: 99%